Determination of Glucocorticoids in UPLC-MS in Environmental Samples from an Occupational Setting - Enrico Oddone; Sara Negri; Massimo Bellinzona; Silvia Martino; Marcello Di Tuccio; Elena Grignani; Danilo Cottica; Marcello Imbriani (International Journal of Analytical Chemistry)
Occupational exposures to glucocorticoids are still a neglected issue in some work environments, including pharmaceutical plants. We developed an analytical method to quantify simultaneously 21 glucocorticoids using UPLC coupled with mass spectrometry to provide a basis to carry out environmental monitoring. Samples were taken from air, hand-washing tests, pad-tests and wipe-tests. This paper reports the contents of the analytical methodology, along with the results of this extensive environmental and personal monitoring of glucocorticoids. The method in UPLC-MS turned out to be suitable and effective for the aim of the study. Wipe-test and pad-test desorption was carried out using 50 mL syringes, a simple technique that saves time without adversely affecting analyte recovery. Results showed a widespread environmental pollution due to glucocorticoids. This is of particular concern. Evaluation of the dose absorbed by each worker and identification of a biomarker for occupational exposure will contribute to assessment and prevention of occupational exposure.